Flexible Lead-Free Piezoelectric Ba0.94Sr0.06Sn0.09Ti0.91O3/PDMS Composite for Self-Powered Human Motion Monitoring - Lin Deng; Weili Deng; Tao Yang; Guo Tian; Long Jin; Hongrui Zhang; Boling Lan; Shenglong Wang; Yong Ao; Bo Wu; Weiqing Yang (Journal of Functional Biomaterials, 2023)
Piezoelectric wearable electronics, which can sense external pressure, have attracted widespread attention. However, the enhancement of electromechanical coupling performance remains a great challenge. Here, a new solid solution of Ba1−xSrxSn0.09Ti0.91O3 (x = 0.00~0.08) is prepared to explore potential high-performance, lead-free piezoelectric ceramics. The coexistence of the rhombohedral phase, orthorhombic phase and tetragonal phase is determined in a ceramic with x = 0.06, showing enhanced electrical performance with a piezoelectric coefficient of d33~650 pC/N. Furthermore, Ba0.94Sr0.06Sn0.09Ti0.91O3 (BSST) is co-blended with PDMS to prepare flexible piezoelectric nanogenerators (PENGs) and their performance is explored. The effects of inorganic particle concentration and distribution on the piezoelectric output of the composite are systematically analyzed by experimental tests and computational simulations. As a result, the optimal VOC and ISC of the PENG (40 wt%) can reach 3.05 V and 44.5 nA, respectively, at 138.89 kPa, and the optimal sensitivity of the device is up to 21.09 mV/kPa. Due to the flexibility of the device, the prepared PENG can be attached to the surface of human skin as a sensor to monitor vital movements of the neck, fingers, elbows, spine, knees and feet of people, thus warning of dangerous behavior or incorrect posture and providing support for sports rehabilitation.